2020
DOI: 10.1038/s41390-020-0824-7
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in neonates with congenital gastrointestinal surgical conditions: a prospective study

Abstract: BACKGROUND: There is limited information on gut microbiota of neonates with congenital gastrointestinal surgical conditions (CGISCs) available. METHODS: This study compared stool microbiota and short-chain fatty acids (SCFAs) of 37 term infants with CGISCs with 36 term healthy infants (HIs). Two stool samples were collected from each infant: as soon as possible after birth (week 1) and 10-14 days of life (week 2). RESULTS: Bacterial richness and alpha diversity were comparable between CGISCs and HIs at week 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
(42 reference statements)
0
8
0
2
Order By: Relevance
“…The stool microbiota was assessed using the 16S ribosomal RNA gene sequencing method (Supplementary File 1 ). Stool short-chain fatty acid assay was performed according to our previously described method 13 with slight modifications (Supplementary File 1 ). The scientists who conducted microbial and SCFA assays and their respective statistical analyses were blinded to the randomisation groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stool microbiota was assessed using the 16S ribosomal RNA gene sequencing method (Supplementary File 1 ). Stool short-chain fatty acid assay was performed according to our previously described method 13 with slight modifications (Supplementary File 1 ). The scientists who conducted microbial and SCFA assays and their respective statistical analyses were blinded to the randomisation groups.…”
Section: Methodsmentioning
confidence: 99%
“… 10 15 Our previous prospective study found that neonates with CGISC develop gut dysbiosis during their stay in the neonatal intensive care unit. 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…По мнению Ra S. C. и коллег (2020 г. ), одним из последствий перенесенной резекции части кишечника у детей является нарушение микробиоты с дефицитом Bifidobacteria и Bacteroides, повышенной распространенностью Escherichia, Shigella и Pseudomonas, а также низкий уровень короткоцепочечных жирных кислот (КЖК) в кале в сравнении со здоровыми детьми [12]. Это может способствовать нарушениям функционирования системы органов пищеварения, ассимиляции питательных веществ, оптимальных процессов роста и развития ребенка в целом [13,14].…”
Section: Introductionunclassified
“…Выявлено снижение темпов роста (длина тела SD: от -1до -2) при низких значениях (<25‰) суммы кислот, при нарастании пропионата (˃25‰) в кале. Снижение питания (масса тела SD: от -1до -2) ассоциировалось с низкими значениями суммы изокислот и АИ (-) (<25‰); к 3 годам жизни риск пониженного питания снижался в 4 раза при высоких значениях (˃75‰) суммы кислот в кале (OR=4,33[1,(9)(10)(11)(12)(13)(14)(15)(16)(17)71]). Разнонаправленность содержания КЖК в кале у детей раннего возраста и их влияние на показатели ФР подчеркивает многогранность функций кишечной микробиоты, оказывающей локальное и системное воздействие на организм человека.Ключевые слова: дети раннего возраста, физическое развитие, метаболическая активность кишечника, короткоцепочечные жирные кислоты.…”
unclassified